Bibliometric Analysis of Ceylon Medical Journal during the period from 2003 – 2012 - Murugathas, K.; Navaneethakrishnan, S. (University Librarians Association of Sri Lanka, 2016)
Ceylon Medical Journal (CMJ) is the premier and oldest medical journal in Sri Lanka. Bibliometric studies on single journals are useful to find out the research trend in a discipline and publication trend of the journal. The objective of the study was to conduct a bibliometric study of CMJ. The study sought to identify co-authorship pattern, geographical distribution of authors, productive institutions, prolific authors, productive articles and the impact of the research work published in CMJ during the study period. The required data of all the selected articles published from 2003 to 2012, related to the analysis were collected from Scopus database. The collected data were analyzed in terms of bibliometric parameters by MS excel 2007 and Bibexcel. The study revealed multi authored articles occupy prominent position indicating cooperative research work. Three author contributions was the highest ranked authorship pattern. Majority (90%) of the authors publishing articles in CMJ were from Sri Lanka. The most prolific author contributed 18 articles during the study period. The most productive article received 57 citations recorded in SCOPUS data-base. University of Colombo and University of Kelaniya were leading institutions in publishing articles in CMJ during the study period. The study highlighted some research trends in health sciences and publishing trends of CMJ. The country distribution of authors showed that the journal reflects the research and views of health researchers mainly from Sri Lanka. The study provides suggestions to improve the impact of the research articles published in CMJ.
Keywords: Bibliometrics; Ceylon Medical Journal; Authorship pattern; Single journal study